Comparison of Antifungal Susceptibility Basil Leaves Extract (Ocimum sanctum Linn.), Eugenol, and Nystatin against Isolates of Candida spp. as Important Agent causing Oral Candidiasis in HIV/AIDS Patient - Emma Hidayati Sasmito; Afif Nurul Hidayati; Rahmadewi; Sawitri; Budi Utomo; Sudjarwo; Pepy Dwi Endraswari; Diah Mira Indaramaya; Dwi Murtiastutik (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2022)
Background: Oral candidiasis is an infection caused by Candida sp. in areas of the oral mucosa that are often found in HIV/AIDS patients. Increased antifungal resistance, it was important to find new antifungal candidates, especially from natural ingredients, basil leaf extract (Ocimum sanctum Linn.) which had major compound of eugenol that had an antifungal effect in inhibiting of Candida sp. Purpose: To evaluate the comparison of the antifungal susceptibility of nystatin, basil leaf extract (Ocimum sanctum Linn.) and eugenol against isolates of Candida sp. Methods: This study examined the comparison of the antifungal susceptibility of nystatin 100 IU, basil leaf extract (Ocimum sanctum Linn.) with doses equivalent to 800 µg/mL and 400 µg/mL eugenol, and eugenol 800 µg/mL and 400 µg/mL against 40 stored isolates of Candida sp. from the oral cavity of HIV/AIDS patient which was reactivated. Result: The mean inhibition zone of nystatin for all isolates was 22.98 mm, while the mean inhibition zone of eugenol with doses of 800 µg/mL and 400 µg/mL were 17.07 mm and 15.89 mm, and the mean inhibition zone of basil leaf extract (Ocimum sanctum Linn.) with doses equivalent to 800 µg/mL and 400 µg/mL eugenol are 14.87 mm and 14.01 mm. The inhibition zone of basil leaf extract (Ocimum sanctum Linn.) and eugenol was significantly lower than nystatin (p = 0.001; p < 0.05). Conclusion: The zone of inhibition of nystatin was significantly higher compared to basil leaf extract (Ocimum sanctum Linn.) and eugenol against Candida albicans and Candida non-albicans isolates.